2020
DOI: 10.1063/1.5126727
|View full text |Cite
|
Sign up to set email alerts
|

Phenomenological modeling of anisotropic dielectric properties in epitaxial (Pb, Sr)TiO3 thin films

Abstract: Strain tuning of polarization states and dielectric properties in (001) epitaxial (Pb, Sr)TiO3 (PST) films is investigated using a thermodynamic phenomenological model. We find that our calculations of anisotropic dielectric properties and their electric field tunability at various in-plane strained states are in good agreement with relevant experimental data for epitaxial Pb0.35Sr0.65TiO3 films when material constants are properly determined. Our modeling further suggests that dielectric tunability can be opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…This difference in chemistry is explained by the fact that the phenomenological thermodynamic potential used in this work may overestimate the stability of the c/a-domain regions as well as provide slight variations of the Curie temperature values for different compositions of strontium. [48,49] Additionally, there are varying reports on the compositions and temperatures at which the Pb 1−x Sr x TiO 3 crystal becomes cubic [50][51][52] which also plays a factor in directly translating the chemistries between simulation and experiment. Considering these numerical and experimental constraints, we believe such differences between the two curves are inconsequential to the main conclusions of the present study and the trends of the data and resulting structures are found to be identical.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This difference in chemistry is explained by the fact that the phenomenological thermodynamic potential used in this work may overestimate the stability of the c/a-domain regions as well as provide slight variations of the Curie temperature values for different compositions of strontium. [48,49] Additionally, there are varying reports on the compositions and temperatures at which the Pb 1−x Sr x TiO 3 crystal becomes cubic [50][51][52] which also plays a factor in directly translating the chemistries between simulation and experiment. Considering these numerical and experimental constraints, we believe such differences between the two curves are inconsequential to the main conclusions of the present study and the trends of the data and resulting structures are found to be identical.…”
Section: Resultsmentioning
confidence: 99%
“…The relevant free energy coefficients and material constants used in the present calculations for the Pb 1−x Sr x TiO 3 thin films were calculated as weighted averages of those for pure PbTiO 3 and SrTiO 3 except for α 1 . [49] A so-called linearly averaged dielectric stiffness α 1 was chosen as was previously used in the literature, [49] that is, www.advmat.de www.advancedsciencenews.com Phase-Field Simulations: To simulate the polarization distribution and domain structure development in the single layer Pb 1−x Sr x TiO 3 thin films, the phase-field method was utilized. The evolution of the polarization structure was governed by solving the time-dependent Ginzburg-Landau equation, that is, , ,…”
Section: Methodsmentioning
confidence: 99%
“…where 𝛼 i , 𝛼 ij , and 𝛼 ijk are the dielectric stiffness coefficients measured under constant stress. For Pb 1−x Sr x TiO 3, the coefficients were calculated as weighted averages of those for pure PbTiO 3 [48] and SrTiO 3 , [49] except for 𝛼 1 where the linearly averaged dielectric stiffness was employed as previously used in the literature: [50] 𝛼 The elastic energy density is expressed as,…”
Section: Methodsmentioning
confidence: 99%